▼Strontium ranelate for osteoporosis?. Issue 4 (1st April 2006) - Unknown
Abstract : In the UK, there are around 200, 000 osteoporotic fractures each year.1, 2 National guidelines in the UK recommend preventative treatment in patients who are at high risk of fracture on the basis of age, fracture history, bone mineral density and other risk factors.1, 2 For secondary prevention, an oral bisphosphonate, such as alendronate or risedronate, is the drug of choice but may not be tolerated, particularly because of unwanted upper gastrointestinal effects.2, 3 Raloxifene provides a potential oral alternative in women.4 National guidelines also suggest subcutaneous ▼teriparatide for women aged more than 65 years with severe osteoporosis who have failed to tolerate or respond to a bisphosphonate;2 however, we believe use of this drug is problematic.5 ▼Strontium ranelate (Protelos - Servier) is a new oral treatment for women with postmenopausal osteoporosis that is promoted as "the first dual action bone agent" and "the only drug to simultaneously increase bone formation and decrease bone resorption". Here we review the evidence for strontium ranelate and consider whether it has a role in postmenopausal osteoporosis.